PERANAN LITOLOGI TERHADAP EROSI PADA DAS CIMANUK BAGIAN HULU - Denny Lumban Raja; Emi Sukiyah; Nana Sulaksana; Cipta Endyana (PPSDM Geominerba, 2020)
The upstream part of the watershed (DAS) extremely affects the downstream area, one of the erosion processes in the upstream and sedimentation processes in the downstream. This must be considered because excess sedimentation from downstream could potentially cause flooding. The rocks in the study area are dominated by volcanic rocks with various levels of resistance to erosion, from highly resistant lava to highly volatile volcanil materials. The research was conducted with studio analysis, laboratory analysis, normalization and correlation tests. The results of the study shows that the area has various values of erosion and sedimentation, because the Cimanuk watershed has various rock types due to volcanism. However, the value of erosion and sedimentation are directly proportional and highly correlated, this proves that indeed erosion in the upstream part highly affects sedimentation in the downstream part of the Cimanuk watershed.